2020
DOI: 10.3390/cancers12113285
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Checkpoint PD-1 in Natural Killer Cells: Expression, Function and Targeting in Tumour Immunotherapy

Abstract: In the last years, immunotherapy with antibodies against programmed cell death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) has shown remarkable efficacy in the treatment of different types of tumours, representing a true revolution in oncology. While its efficacy has initially been attributed only to unleashing T cell responses, responsivity to PD-1/PD-L1 blockade was observed in some tumours with low Human Leukocyte Antigen (HLA) I expression and increasing evidence has revealed PD-1 surface expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 153 publications
(171 reference statements)
4
68
1
Order By: Relevance
“…Recently, our group and others reported that ILC2s facultatively express PD-1 and PD-L1 when activated with alarmin cytokine IL-33 (8,17,18). And indeed consistent with T, NK and B cells, engagement of PD-1 on ILC2s dramatically downregulates proliferation, viability and effector function (19)(20)(21). Conversely, inhibition of PD-1 engagement results in increases in total ILC2 number, increased production of cytokines, and overall cell function (8,17,18).…”
Section: Introductionmentioning
confidence: 73%
“…Recently, our group and others reported that ILC2s facultatively express PD-1 and PD-L1 when activated with alarmin cytokine IL-33 (8,17,18). And indeed consistent with T, NK and B cells, engagement of PD-1 on ILC2s dramatically downregulates proliferation, viability and effector function (19)(20)(21). Conversely, inhibition of PD-1 engagement results in increases in total ILC2 number, increased production of cytokines, and overall cell function (8,17,18).…”
Section: Introductionmentioning
confidence: 73%
“…The consequences of PD-1 signaling for NK cells are incompletely understood, albeit there is accumulating evidence that in addition to T cells, NK cells contribute to the promising antitumor effects of PD-1/PD-L1 checkpoint inhibitors [ 29 , 30 , 46 , 47 ]. Accordingly, we hypothesize that significantly lower levels of PD-L1 in Cdk8-knockdown cell lines are in part responsible for eliciting a stronger NK-cell-mediated antitumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Besides CD16 (FcĪ³IIIa receptor) that recognizes Fc fractions of several IgG subclasses and is responsible for the antibody-dependent cell-mediated cytotoxicity (ADCC) ( 48 ), the Natural Cytotoxicity Receptors (NCR) NKp30 (CD337, the product of the ncr3 gene), NKp44 (CD336, the product of the ncr2 gene), NKp46 (CD335, the product of the ncr1 gene) and NKp80 (the product of the klrf1 gene), together with DNAM-1 (CD226) and NKG2D (CD314, the product of the klrk1 gene) emerged as a major activating receptors ( 17 , 37 , 49 ā€“ 52 ). In vivo blockade of NKG2D or NKG2D knock out mice leads to an increased susceptibility to spontaneous tumor development and tumor progression ( 53 , 54 ).…”
Section: The Nkg2d Receptor and Its Ligandsmentioning
confidence: 99%
“…The possibility to phenotypically characterize dysfunctional TINK generated a renewed interest in targeting co-inhibitory receptors to reinvigorate NK cells in cancer patients using current or novel ICI ( 174 ). Targeting the PD-1/PD-L1 axis, CD96 (TACTILE), NKG2A, TIGIT, TIM-3 and LAG-3 have emerged as forefront alternatives because they are usually over-expressed in dysfunctional NK cells ( 33 , 52 , 175 ā€“ 179 ). Although the revolution in I-O achieved with ICI was originally attributed to an enhanced T cell-mediated antitumor response, increasing evidence demonstrates that NK cells also express PD-1 and PD-L1, and that they constitute targets of ICI that results in a reinvigoration of anti-tumor NK cell effector functions.…”
Section: Nk Cell Reinvigoration Through Targeting Co-inhibitory Receptorsmentioning
confidence: 99%